DIGITALIZATION AS AN ENGINE OF ECONOMIC GROWTH - Natalia V. Rudyk,; Shakizada Niyazbekova,; Oksana F. Viliguta,; Tamara Yu. Dzholdosheva,; Kaldenova Gulzhanat Sidicovna,; Zhanabayeva Zhanar Kairbekovna, (Scientific Journal of Pedagogy and Economics, 2021)
The analysis of modern publications on the stated problem suggests a great interest of the scientific community about the digital development of economic systems at various levels. However, the Russian experience of developing and implementing digital technologies has not been studied well. As a result, Russian features of digital economy development and systematization of existing approaches provide a great scientific and practical interest. It is noted that the digital economy, which generates a continuous stream of innovations, involves the development of human capital, which, in turn, requires a systematic approach to knowledge management. The development of the digital economy in Russia is declared as one of the most important directions of state policy and is considered as a prerequisite for competitiveness in the modern global market and a strategic component of the state's economic sovereignty. An organization that embarks on a digital transformation strategy needs a vision of its final achievement, and that vision should be more than a statement on the website. For the transformation to be successful, the organization must adapt its vision every day, and employees must know the way of their contribution. To make digital transformation real, you need a vision and ability to do it. Digital solutions, meanwhile, represent digital products or services – for example, a medical platform that connected to Phillips or GE's offerings on the industrial Internet. The results of the study: The analysis of the digital economy of the Russian Federation was carried out. The main directions in solving the identified problems of digitalization in Russia were Proposed. The methodological basis of the research is the scientific works of Russian and foreign scientists in the field of the digital economy, the results of various applied research on the formation of the knowledge economy.